Atviros Lietuvos knyga ekspertų požiūriu - Poviliūnas, Arūnas (Knygotyra, 2003)
Evaluation of the academic literature publishing in Lithuania was twofold. Some of the experts estimated situation as critical, others stressed the obvious improvement in the field of academic publishing. Skeptics appealed to the state authorities, which do not have clear policy of academic publishing and moreover, do not give support to it. Optimists enjoyed newly published books and doubted ability of the state authorities to coordinate academic publishing. Intellectual and academic discourses are constructed from the local knowledge and the totality of it cannot be grasped from one generalizing point. But experts agreed that limited resources determine the need of clear priorities in academic publishing. The publishing of the intellectual and academic literature face different problems that come from its specific conditions. An academic book is more expensive because its number of copies and circulation is smaller. The reader of an academic book is more educated, knows foreign languages and this limits the market of academic translations. Academic field is specialized and it requires very different and special texts. Academic texts, this is based on the special traits of academic field, have longer period of consumption and this also causes additional finance problems for publishers. All experts agreed that Programme The Books for an Open Society is very important for academic publishing and helps solving the problems that it faces nowadays. The Programme helped publishers of academic, non-commercial literature to begin their work. Experts thought that main target reader of the Programme The Books for an Open Society books is contemporary and future intellectual elite. But academic, intellectual society is very fragmented and differs by academic disciplines and degree of socialization into academic community, etc. Moreover, big part of potential readers of Programme book has rather narrow specialization and "lives" in its own professional "cell". At the same time, there is competition between academic groups that causes marketing problems for publishers. But younger generation of academic community is more mass consumer of academic literature. Experts agree that the Programme The Books for an Open Society reflects general tendencies in social and humanitarian sciences, but stressed that there are factors that influence this reflection. These factors are ideological priorities of the Programme, more attention to Anglo-Saxon tradition, not equal sympathy for different academic disciplines. Experts also stressed that publishing of nonfiction translations always will be retarded because only the books that are already recognized in Western academic community are selected for translation and publishing. Further discussion proved that Programme The Books for an Open Society is an organic part of Lithuania’s academic field and at the same time reflects all its subtleties. Discussion of experts about the quality of the Programme’s books concentrated on the quality of translations. Discussion demonstrated that there is a non-cooperational relationship between publishers and editors on the one side and translators on the other and this situation inevitably influences the quality of the published book. It came out, that the Programme did not find a way out of this problematic situation. Pilot translations as such could not change the situation and they often remained only a way to control. But experts recognized that the publishing activities of the Programme The Books for an Open Society and Open Society Fund-Lithuania in general were very important in raising good new translators. Experts mentioned following shortages of the Programme The Books for an Open Society: (1) The Programme by being ideologically engaged, inevitably supported only some of academic tendencies; (2) The Programme could have supported original Lithuanian books and textbooks. This could enrich the academic discourse already opened by translations; (3) Experts noticed that the Programme favours some academic disciplines at the cost of others; (4) Experts thought that the Programme also favours fundamental academic publications at the cost of more ephemeral but popular academic books; (5) Some facts from books publishing proves that criteria used in selecting books for publishing under the Programme title are not clear enough. Experts also discussed the possible reasons that caused mentioned shortcomings of the programme, especially the quality of translations. One of reasons was that institutional resources of publishing houses during the accomplishment of the Programme were not enough to realize the possibilities which have appeared when OSF-L publishing programmes (The Books for an Open Society and publishing activities of the Programme Education for the Future of Lithuania) have joined the publishing market of Lithuania. The lack of institutional resources for the effective use of the new financial possibilities sometimes has negatively influenced the quality of the published books. Experts recommend to pay more attention to the publishing of dictionaries of social sciences and humanities – more summarizing, synthesizing books, which would represent achievements not only of Anglo-Saxon tradition. Proportions between published books of different academic disciplines are to be followed more precisely. Especially in publishing dictionaries, new technologies could be used more often (CD-ROM etc.).